Levantamento cienciométrico de publicações científicas sobre cultivo in vitro e aclimatização de orquídeas do cerrado - Almeida, Loury Lay Gomes (Universidade Federal do Tocantins, 2025)
Scientometrics is a study that analyzes each area of knowledge taking as a parameter time, region, institutions and their respective communities, thus allowing an understanding of several areas. The objective of this work was to carry out a systematic review to evaluate the scientific production of the last twenty years on the subject of in vitro cultivation of orchids occurring in Cerrado areas. Three databases were used for the search: CAPES Periodicals, Scopus, and Web of Science. The following terms were used for data collection: “in vitro”, “in vitro culture”, “micropropagation”, “acclimatization”, being combined with "orchid and Cerrado " and "orchid and savanna" with a total of eight combinations. The Boolean operator "AND" was employed. All selected articles were subjected to the inclusion and exclusion criteria. A total of 36 peer-reviewed articles were found between the periods 2001 and 2021, with a greater number of publications being analyzed in the years 2020 and 2021. The studies done on in vitro culture and acclimatization of orchids from the Cerrado in the last decades is relatively low when compared to indexed journals. Studies of in vitro culture techniques not only have a great relevance for forestry and economic practice, but for science as a whole.